Uso de complexo multienzimático em dietas com grãos secos de destilaria com solúveis para suínos de crescimento e terminação - Dantas, Thamires Allue (2020)
Distillers dried grains with soluble (DDGS) have up to three times more fiber than corn, which results in less digestibility of this co-product and consequently less energy availability. Therefore, the involvement of exogenous enzymes that can degrade fiber is beneficial for improving the use of DDGS. In this sense, the objective was to evaluate the inclusion of a multienzyme complex (MC) in diets based on corn and soybean meal, with or without inclusion of DDGS. The experiment was performed in the Experimental Center on pig farming at the Department of Animal Science of the Federal University of Lavras, in Lavras, MG, Brazil, using 144 pigs of 38.83 ± 1.59 kg in the growth phase and 88 pigs of 89.28 ± 2.78 kg in the finishing phase. The experimental design was in randomized blocks (initial weight) and the pen used as an experimental unit. Four experimental diets were tested, one basal diet (BD) formulated based on corn and soybean meal, another containing DDGS (15% in the growth phase and 25% in the finishing phase), another containing the MC and another containing the DDGS + the MC. The diets were isoenergetic and formulated accord the nutritional requirements of the animals. There were no differences (P>0.05) in the animals' performance. The apparent digestibility coefficient (CDA) of nutrients in diets with DDGS was lower (P<0.05) compared to the others. The inclusion of CM improved (P<0.01) the CDA of dry matter, crude protein, crude energy, and neutral detergent fiber, as well as the total and ileal digestibility of some amino acids in diets with DDGS. Higher amounts of beneficial bacteria were observed in animals that received RB, while diets containing only DDGS increased (P<0.05) the number of pathogenic bacteria and worsened the richness of biodiversity. The use of MC increased (P<0.001) the number of Bifidobacterium and reduced (P<0.001) bacteria of the genus Streptococcus, in addition to increasing biodiversity (P<0.05). It is concluded that the inclusion of 15 or 25% of DDGS, respectively, in diets for growing and finishing pigs, can be used if associated with a commercial multienzyme complex.